Early Intervention Techniques for Toddlers with Language Delays: A review of Literature - Srivastava, Anuj (International Journal of Psychosocial Rehabilitation, 2020)
Speech and Language development is a very useful indicator of child’s overall development and cognitive ability. Early language delay is common in toddlers with special needs. Language delay in toddlers is related to reading difficulties, persistent communication problems and lately poor academic outcomes. It is found that few early interventions techniques for toddlers with early language delays yield positive receptive and expressive language results. This study aimed to target on those manifold Early Intervention techniques for toddlers with language delays. This study a literature reviews of varied researches exhausted this area.